Novos diterpenos dos frutos de Xylopia langsdorffiana - Duarte, Marcelo Cavalcante (2009)
Xylopia langsdorffiana (Annonaceae) is popularly known as pimenteira da terra in the Northeast region of Brazil. Previous studies have reported the presence of alkaloids and diterpenes isolated from the leaves and/or stem of X. langsdorffiana. This work aimed to continue the phytochemical study of this species, using its dry and fresh fruits. Initially, the dry and powdered fruits were submitted to maceration with methanol (95%) and the extractive solution obtained was concentrated in rotatory evaporator yielding 200g of extract. A portion (150g) of the latter was partitioned with hexane, dichloromethane and ethyl acetate. The isolated chemical constituents were identified through the analysis of data obtained by spectroscopic methods such as Infrared and one-dimensional 1H, 13C Nuclear Magnetic Resonance with two-dimensional techniques (COSY, NOESY, HMQC and HMBC), besides comparison with literature data. Seven diterpenes were isolated from the hexane and dichloromethane phases of the fruits of X. langsdorffiana, being four of them known in the literature ent-atisan-7α, 16α-diol (xylodiol), ent-7α-hydroxytrachyloban-18-oic acid, 13-epicupressic acid, ent-kaur-16-en-3β, 19 diol, and 3 new diterpenes ent-3β- hydroxy-labda(8)17,12Z-, 14-trien-18-oic acid, (Labdorffianic A Acid), ent-Labda 8(17)epoxy, 14 en-18-oic Acid (Labdorfianic B Acid) and ent-Labda 8(17) epoxy, 13(16), 14-Dien-18-oic acid (Labdorfianic C Acid). Since some species of Annonaceae are known to possess significant amounts of essential oils, we decided to analyze the fresh fruits of X. langsdorffia in order to obtain and analyze its essential oil. Therefore, its fresh fruits were extracted by hydrodistillation in a Clevenger apparatus and characterized with GC-MS, showing a constitution of monoterpenes (66.6%), sesquiterpenes (33.3%) and diterpenes (11.11%), being the α-pinene(37.73%) and limonene (31.42%) the major constituents. Spathulenol (1.59%) which is considered the marker for Xylopia was also detected. Thus, the results obtained in this work contributed to broaden the chemical knowledge of species of Annonaceae, especially Xylopia langsdorffiana.